OVERVIEW OF STUDIES ASSESSING THE ECONOMIC IMPACT OF MICRONUTRITIONAL FORTIFIERIZATION IN FOOD (Vietnam Journal of Community Medicine, 2026)
Objective: Micronutrient deficiencies are a significant public health problem, causing substantial economic losses in many countries. Fortifying food with iron, iodine, and zinc is a widely recommended preventive measure, but policy implementation in some contexts remains challenging. This study aims to synthesize international evidence on the economic impact of the aforementioned three micronutrient fortification programs.Methods: A desk study was conducted using data from two databases, PubMed and Google Scholar, to screen relevant studies and synthesize key findings.Results: Evidence suggests that micronutrient fortification programs offer significant economic benefits. Iron fortification has a benefit-cost ratio ranging from 6:1 to 36:1 in different study contexts. The universal salt iodization program recorded a benefit-cost ratio of up to 30:1 and significantly reduced the burden of iodine deficiency disorders. Zinc fortification, particularly in countries with high wheat consumption, also showed positive effects with a benefit-cost ratio of approximately 14.6:1.Conclusion: The combined evidence suggests that micronutrient fortification in food is a preventative health intervention with significant economic benefits. The results may support the review, adjustment, and improvement of policies to strengthen micronutrient fortification in Vietnam.
Keywords: Economic impact, micronutrient fortification, iron, iodine, zinc, cost-effectiveness.